Optimisme Masa Depan pada Narapidana Kasus Pembunuhan ditinjau Berdasarkan Dukungan Sosial dari Keluarga di LAPAS Klas IIA Kota Padang - Repormei Wandri; Krisnova Nastasia; Rina Mariana (Psyche 165 Journal, 2021)
The research is aimed to know the relationship between a social support of families with optimism the future of the inmate 's murder at the Lapas Klas IIA Kota Padang . The independent variable in this study is social support and the dependent variable is optimism . The measuring instrument used in this study is scale social support and optimism scale . Mechanical taking samples in the study is using the technique of saturated samples . Samples in research this is 38 people inmate cases killings at the Lapas Klas IIA Kota Padang . The validity and reliability test in this study uses the Cronbach Alpha technique . The results of the coefficient of the validity of the scale of social support moves from r ix = 0.30 9 until the r ix = 0, 689 with the coefficient of reliability of α = 0.9 14 while on a scale of optimism moving from r ix = 0.3 09 up to r ix = 0.799 with the co efficient of reliability of α = 0.9 35 . Based on data analysis , a correlation value of 0, 928 was obtained with a significance level of 0.000, which means the hypothesis was accepted. This shows that there is a significant relationship between social support from the family and optimism in the murder convicts in Lapas Klas IIA Kota Padang .